Ourselves and Others Scotland 1832-1914 - Morton, Graeme (New History of Scotland : NHS, 2022)
What does it mean to be a Scot and what forged that identity?Read and download the first chapter from Ourselves and Others: Scotland 1832-1914 for free now (pdf)This revised and updated volume of the New History of Scotland series explores a period of intense identity formation in Scotland. Examining the 'us and them' mentality, it delivers an account of the blended nature of Scottish society through the transformations of the industrial era from 1832 to 1914.Alongside the history of Scotland's national identity, and its linked political and social institutions, is an account of the changing nature of society within Scotland and the relentless eddy of historical developments from home and away. Where previous histories of this period have focused on industry, this book will take a closer look at the people that helped to form Scottish national identity. Graeme Morton shows that identity was a key element in explaining Industrial Scotland, charting the interplay between the micro and the macro and merging the histories of the Scots and the Scottish nation.Graeme Morton is the Scottish Studies Foundation Chair and Director of the Centre for Scottish Studies at the University of Guelph.Key FeaturesPopular and well-liked student seriesCompletely updated and revised with new researchCharts the birth of modern Scottish identity 1832-1914Emphasis on weather, sport, leisure, consumption and material culture of childhood